Aromaterapi Lavender terhadap Intensitas Nyeri Haid (Dysmenorrhea) pada Mahasiswi Tingkat II - Rina Nuraeni; Arin Nurholipah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the effect of lavender aromatherapy on the intensity of menstrual pain (dysmenorrhea) in Level II female students at STIKes YPIB Majalengka. The research method is pre-experimental research with one group pretest-posttest design. The results showed that less than half (35.0%) of menstrual pain intensity before lavender aromatherapy was severe. Less than half (40.0%) of the power of menstrual pain after lavender aromatherapy was moderate. There is an effect of lavender aromatherapy on the intensity of menstrual pain (dysmenorrhea) in second-level female students at STIKes YPIB Majalengka (p = 0.001). In conclusion, lavender aromatherapy affects the intensity of menstrual pain (dysmenorrhea) in female students. Keywords: Lavender Aromatherapy, Dysmenorrhea, Adolescent Girls